2022
DOI: 10.14336/ad.2021.0731
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 and Cognitive Disorders

Abstract: Aquaporin-4 (AQP4) is the most abundantly expressed aquaporin in the central nervous system (CNS) and is an integral part of the glymphatic system that cannot be ignored. The CNS has the glymphatic system instead of the conventional lymphatic system. The glymphatic system plays an essential role in the pathophysiological processes of many cognitive disorders. AQP4 shows noteworthy changes in various cognitive disorders and is part of the pathogenesis of these diseases. For this reason, AQP4 has attracted atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…An EEG study with transgenic mice demonstrated a close correlation between neuronal accumulation of synuclein and slowing of brain oscillations and changes in network excitability [22,41]. Studies have shown that the complex interaction between cholinergic and other transmitter systems participates in the pathophysiological mechanism of brain electricity slowing and cognitive decline in neurodegenerative diseases [42][43][44][45][46]. Other studies and our results suggest that QEEG is a valuable tool to assess the electrophysiological changes related to cognitive impairment or dementia [47].…”
Section: Discussionsupporting
confidence: 62%
“…An EEG study with transgenic mice demonstrated a close correlation between neuronal accumulation of synuclein and slowing of brain oscillations and changes in network excitability [22,41]. Studies have shown that the complex interaction between cholinergic and other transmitter systems participates in the pathophysiological mechanism of brain electricity slowing and cognitive decline in neurodegenerative diseases [42][43][44][45][46]. Other studies and our results suggest that QEEG is a valuable tool to assess the electrophysiological changes related to cognitive impairment or dementia [47].…”
Section: Discussionsupporting
confidence: 62%
“…Biondi ring tangles, lipofuscin deposits and lipid droplets rich in oleic acid side chains selectively accumulate in the ependymal cells, ultimately leading to the deterioration of the neurogenic niche of the SVZ, further suppressing neurogenesis and destroying striatal and hippocampal function [54]. Aquaporins such as AQP1 expression and CSF secretion were also diminished [122,123]. By using an unbiased proteomic analyses on autopsy tissue from AD, 25 proteins were found to be significantly increased on the lateral ventricle walls, including amyloid-β , indicating abnormalities in the clearance of some toxic molecules and a decrease in CSF turnover around the ependyma in AD pathology [124].…”
Section: Ependymal Cells In Aging and Alzheimer's Diseasementioning
confidence: 99%
“…AQP4 is a water channel highly polarised in the astrocytic end-feet fringing perivasculature basal membranes [ 34 ] that regulates tonicity-responsive cross-membrane transport of water [ 38 ]. In physiological conditions, AQP4 is crucial for efficacious glymphatic movement and CSF clearing [ 39 , 40 , 41 ] via transastrocytic bulk flow [ 42 ], as the majority are localised so that APQ4 are connected to adjacent perivascular spaces, enabling CSF flow between this and the cerebral parenchyma [ 15 ]. Here, the admixture of CSF and interstitial fluid (ISF) occurs, which then travels to subarachnoid spaces where the CSF-ISF then infiltrates into the lymphatic or bloodstream vessels [ 42 ].…”
Section: Glymphatic System and Alzheimer’s Diseasementioning
confidence: 99%
“…In physiological conditions, AQP4 is crucial for efficacious glymphatic movement and CSF clearing [ 39 , 40 , 41 ] via transastrocytic bulk flow [ 42 ], as the majority are localised so that APQ4 are connected to adjacent perivascular spaces, enabling CSF flow between this and the cerebral parenchyma [ 15 ]. Here, the admixture of CSF and interstitial fluid (ISF) occurs, which then travels to subarachnoid spaces where the CSF-ISF then infiltrates into the lymphatic or bloodstream vessels [ 42 ]. As a result, this facilitates a drainage/clearance mechanism of the ISF and, notably, the removal of waste products such as Aβ [ 43 ].…”
Section: Glymphatic System and Alzheimer’s Diseasementioning
confidence: 99%